Comparison study: different grades of emesis in different dose intensities of Epirubicin in early stage breast cancer patients undergo FEC / Zaid Khalid and Norain Mokhtar - Khalid, Zaid; Mokhtar, Norain (2010)
Epirubicin has not yet been fully clarified but it is probably related to its ability to bind with DNA. Cells culture studies have shown cell penetration, localisation in the nucleus and inhibition of nucleic acid and mitosis. Epirubicin is indicated for the treatment of breast cancer, gastric cancer, ovarian cancer, small cell lung cancer, lymphoma and superficial bladder cancer. This study which entitled Different Grades of Emesis in Different Epirubicin Dose Intensities in Early Stage Breast Cancer Patients Undergo FEC (5-FU, Epirubicin and Cyclophosphamide) Chemotherapy Regime,is mainly aiming in rationalizing the use of Epirubicin regimen in higher dose intensity as it may produce less and well tolerated side effects (emesis) but at the mean time represents highly significant difference in therapeutic outcomes compared to lower dose intensity regimen of epirubicin in combating advanced breast cancer. The study indicates four main objectives which include determination of grades of emesis, assessment of the frequency of patients in different dose intensities of epirubicin, comparison of side effects generated by different dose intensities of epirubicin and lastly, establishment of correlation between increments of epirubicin dose intensity to the level of emesis occurrence. The study was conducted on 90 early stage breast cancer patients in the HTJS Day Care Unit. The data were collected from Patient Monitoring Form starting from January 2007 to December 2009. As from the results obtained, zero grade of emesis shows a none-significant decrement as the dose intensifies from 80mg/m2, 90mg/m2 and lOOmg/iTf which the frequencies are ranging from 27%, 23% and 17% respectively. However, for the first grade of emesis clarifies a none-significant increment of frequencies from 30%, 43% and 47% in that order. Meanwhile for the second grade of emesis, the result fluctuates from 27%, 20% and 27%. And last, the third grade of emesis dictates decrement in the frequencies of patients from 17%, 13% and 10% correspondingly. This shows that there is decrement and also increment in the episodes of emesis as the dose of epirubicin is intensified, but the alteration in the episodes of emesis is still not significant to be considered. . In concise, this study suggests that a higher dose of epirubicin can be considered if lower dose of epirubicin is not working. Even if the dose is intensified, the side effects are still well tolerated by most patients but might increase the possibility of having long term side effects like cardiac toxicity if only the regime is practiced for a long term use.